PERANAN SASTRA INDONESIA DALAM MEMBANGUN KERAGAMAN BUDAYA: PERSPEKTIF SEJARAH - Wilda Fizriyani (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Dulce et utile is not an odd word in literary world, Dulce et utile is not an odd word to the world of literature, because it is the function of literature. A literary work which  is  born  as  the  graffiti  of  the  writer  has  a  goal  to  be  entertaining  and  useful  to readers. The benefit is the reader can get many forms of messages, such as moral, religious, even culture. Such as works of Pramoedya Ananta Toer is considered to be influencing the things that are not good for the reader. This can be explained that literary works actually have the ability to affect the "thought dimension" and socio-cultural of society. This paper describes how the literature can have a cultural influence in Indonesia in terms of history.